2012
DOI: 10.1371/journal.pone.0038437
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Enhance the Conservation-Compatibility of Solar Energy Development

Abstract: The rapid pace of climate change poses a major threat to biodiversity. Utility-scale renewable energy development (>1 MW capacity) is a key strategy to reduce greenhouse gas emissions, but development of those facilities also can have adverse effects on biodiversity. Here, we examine the synergy between renewable energy generation goals and those for biodiversity conservation in the 13 M ha Mojave Desert of the southwestern USA. We integrated spatial data on biodiversity conservation value, solar energy potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 23 publications
0
68
0
1
Order By: Relevance
“…The landscape-scale Desert Renewable Energy Conservation Plan initially provided a siting frameworkincluding incidental take authorizations of endangered and threatened species-for streamlining solar energy development within the 91,000 km 2 of mostly desert habitat in public and private lands and designated as the Development Focus Area (DFA). After accounting for unprotected environmental attributes like biodiversity, Cameron et al (14) identified ∼7,400 km 2 of relatively low-value conservation land within the Mojave Desert Ecoregion (United States) that can meet California's 33% renewable portfolio standard for electricity sales seven times over. Since this publication, the Desert Renewable Energy Conservation Plan's DFA has now been restricted to only public lands, which some argue to be more intact, and to the ire of certain local interest groups and government agencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The landscape-scale Desert Renewable Energy Conservation Plan initially provided a siting frameworkincluding incidental take authorizations of endangered and threatened species-for streamlining solar energy development within the 91,000 km 2 of mostly desert habitat in public and private lands and designated as the Development Focus Area (DFA). After accounting for unprotected environmental attributes like biodiversity, Cameron et al (14) identified ∼7,400 km 2 of relatively low-value conservation land within the Mojave Desert Ecoregion (United States) that can meet California's 33% renewable portfolio standard for electricity sales seven times over. Since this publication, the Desert Renewable Energy Conservation Plan's DFA has now been restricted to only public lands, which some argue to be more intact, and to the ire of certain local interest groups and government agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Siting USSE installations in places already impacted by humans (e.g., parking lots, rooftops) reduces the likelihood that adverse environmental impacts will occur and can exceed generation demands for renewable energy goals in places with moderate-to high-quality solar resources (8,10,13), including California. When sites within the built environment are inaccessible, siting that minimizes land use and land cover change within areas acting as carbon sinks, avoids extirpation of biodiversity, and does not obstruct the flow of ecosystem services to residents, firms, and communities, can serve to mitigate adverse environmental impacts (2,3,9,10,14,15). Siting within the built environment also reduces the need for complex decision making dictating the use of land for food or energy (16).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The most common method is to modify the weighting obtain from the experts, while the assumption of equal weighting is also used (Cameron et al, 2012). In this project, the sensitivity analysis performed considers the effect of changes of criteria weights upon the overall suitability index.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Other risks to wildlife from solar park operation include chemicals such as dust suppressants and rust inhibitors (Hernandez et al, 2014). Water is also used to clean the panels, which may pressurize scarce resources in dry regions (Cameron et al, 2012). It is also important to take into account the life-cycle assessment: processes involved in obtaining rare materials used for making solar panels may lead to biodiversity impacts elsewhere, e.g., at the source of extraction (European Commission, 2014).…”
Section: Introductionmentioning
confidence: 99%